Regulation of casein micelles dissociation by sodium tripolyphosphate to improve gel properties as stabilizers and protein fortifier for high-protein yogurt - Zi-Ying Zhao; Zi-Wei Liu; Bo-Kang Yu; Ying-Chao Qiu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Exploring immunomodulatory peptides derived from bovine colostrum protein based on QSAR models: preparation, identification, in vitro activity, and molecular docking analysis - Ying-Chao Qiu; Zi-Ying Zhao; Stella Zhu; Meng-Jiao Wang; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Surface-confined AlOxFy on thermal shock-generated α-Al2O3 for coke-resistant dehydrofluorination of 1,1-difluoroethane - Zhenxiang Li; Yongchao Zhao; Fengqing Hu; Zaizhe Cheng; Keyi Mu; Yuchen Chen; Aimin Chen; Zongjian Liu; Ying Li; Wujian Zhang; Haodong Tang (Chemical Engineering Journal, 2026)

Dual-aptamer-activated RCA-MOF synergistic platform for visual detection of leukemia-derived exosomes - Ying Shen; Yunlong Xiao; Lu Liu; Suzhen Zhai; Renwu Mu; Jiahui Chen; Xiaoyan Yang; Xiaojun Wen; Chunlin Zhang; Hai Shi (Analytica Chimica Acta, 2026)

Deciphering mechanisms of environmental adaptation, antibiotic tolerance, and potential virulence traits of Pseudomonas baetica isolated from anthropogenic habitat - Mu-Qi Zhang; Yi-Cheng Wang; Ming-Ying Mao; Yin-Qiu Qin; Peng Yan; Hui-Min Fu; Yuan-Xiang Mao; Ji-Cheng Liu; You-Peng Chen; Meng-Jiao Gao (Journal of Environmental Chemical Engineering, 2026)

Enhancing composite emulsion stability through electrostatic modulation of polysaccharides-whey protein isolate interactions for probiotic encapsulation - Wei-Gang Xin; Yu-Hang Jiang; Yu-Han Dong; Yu-Hang Hou; Mu-Ying Du; Amel Ahmed Ibrahim; Zsolt Zalán; Hua-Yi Suo (Food Chemistry, 2026)

Limited enzymatic hydrolysis reshapes whey protein antigenicity, taste profile, and techno-functional properties - Meng-Qi Liu; Wen-Qi Liang; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Protein glutaminase–mediated deamidation improves the hydration properties of spray-dried micellar casein powders by coupling hierarchical porosity with surface charge and hydrophobicity modulation - Yi-Fang Gao; Stella Zhu; Di Su; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2026)

Injectable bioresponsive nanocomposite hydrogels for ROS scavenging and immunomodulation to accelerate diabetic bone repair - Zijian Wang; Wei Jin; Ying Zhou; Jieying Zhang; Xinkun Shen; Caiyun Mu; Maowen Chen (Chemical Engineering Journal, 2026)

Investigation, Evaluation and Geoconservation of the Yardang Landforms in Dahaidao Region, Hami Basin, Xinjiang, NW China - Qing-Wei Song; Hong-Xu Mu; Zhao-Jie Chen; Xu-Dong Song; Xiu-Long Zhang; Ying Dong; Yi-En Xiao (Geoheritage, 2026)

METTL18-catalyzed histidine methylation of YTHDF2 promotes mRNA stability - Wen-Lan Yang; Meng-Xia Liu; Yue Han; Xing-Xing Li; Ye Gu; Xinyuan Tian; Mengqian Mu; Xiaolin Zhang; Yanzhe Wang; Xinyu Li; Yu-Sheng Chen; Chun-Chun Gao; et al. (Science China Life Sciences, 2026)

Combined exposure to flumethrin and hexaconazole induces synergistic oxidative, metabolic, and immune dysregulation in honeybees - Tao Cang; Ying Wang; Xinfang Li; Xin Peng; Qihe Zhao; Xiyan Mu; Guojun Zhou; Yanhua Wang (Journal of Hazardous Materials, 2026)

Deciphering the mechanisms underlying regional heterogeneity of high-temperature Daqu through integrated electronic sensory, volatilome, and microbiome analysis - Yu Mu; Hong Zhang; Yingdong Pan; Ziyou Tian; Ying Huang; Liang Yang; Chunlin Zhang; Chi Zhao; Dong Li; Xudong Liu; Li Jiang (International Journal of Food Microbiology, 2026)

Zwitterionic imprinting enables fouling-resistant biomimetic sensing of Staphylococcus aureus in complex food matrices - Zhi Zeng; Manru Zhao; Zhongrui Ma; Yufei Mu; Xiaoya Li; Yanqun Wang; Ying Chen (Food Chemistry, 2026)

Cl−-repelling Mn3O4/Co(OH)2 heterojunction on self-supporting N-doped CNTs for high-stability seawater zinc-air batteries - Lin Mu; Yuxin Yao; Haibo Zhao; Shifang Yang; Ying Wang; Peng Yu (Chemical Engineering Journal, 2026)

ROS regulate pollen germination and tube growth in Betula platyphylla with involvement of H2O2 and polyamine oxidase BpPAO2 - Chaoning Zhao; Wendi Mu; Jiaqi Shi; Jiayuan Shi; Bello Hassan Jakada; Gege Dou; Taihe Zhao; Huiyi Xie; Siyu Dong; Ying Wu; Xingguo Lan (Physiology and Molecular Biology of Plants, 2026)

Source apportionment of heavy metals via PMF-space auto-correlation and source-oriented human health risk assessment: identification of priority control factors - Minghao Li; Jingyu Mu; Chengqi Zhang; Kai Ye; Ying Luo (Environmental Geochemistry and Health, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Integrating network pharmacology, molecular dynamics, and in vitro assays to unveil the mechanism of costunolide against gastric cancer - Chaohong Zhu; Qiuxiong Chen; Ying Li; Hui Wu; Qijun Ming; Mengyue Ma; Junjie Mu; Xiaoqin Long; Xian Yang; Xue Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Discovery of rare cycloartane-type triterpenoid sulfates from Wrightia pubescens and their neuraminidase inhibition activity - Xingxiang Chen; Jinpeng Lv; Yu Mu; Ying Jiang; Xueshi Huang; Li Han (Phytochemistry, 2026)

Hepatic Sirt2-PARP1-HMGB1 axis promotes exercise-mediated amelioration of MASH in mice - Shan Li; Wang-Jing Mu; Zi-Ang Zhao; Wan-Qiu Peng; Jie-Ying Zhu; Ruo-Ying Li; Lin-Jing Yan; Yang Li; Hong-Yang Luo; Min Chen; Meng-Ting Yin; Xin Li; et al. (Science China Life Sciences, 2026)

From intention to action under institutional nudges: governmental pathways to climate adaptation technology adoption in rural China - Lan Mu; Ying Li; Haoying Liu; Qiongyao Wang; Meimei Wang (Journal of Rural Studies, 2026)

Stage-specific environmental responses and divergent distributional shifts of Antarctic krill under climate change in the Cosmonaut Sea - Xiuxia Mu; Xianyong Zhao; Chongliang Zhang; Yunxia Zhao; Qingchang Xu; Jichang Zhang; Yiping Ying; Lu Liu; Jianfeng He; Peiru Luo; Xinliang Wang (Journal of Environmental Management, 2026)

Predictive Multi-Physics coupling coal combustion model under rapid heating - Hanjian Li; Ying Zhao; Shichen Ding; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Huanying Chi (Fuel, 2026)

Development of 3D bioprinted medulloblastoma organoid model based on ternary bioink with high drug resistance and tumor migration - Wenjun Liao; Yiyu Wang; Ying Li; Yan Zhu; Yuanbo Tu; Xue Mu; Xiwen Zhang; Yiwei Liu; Yaolong Wang; LiFeng Kang; Jinfu Diao; Chunyong Wu; et al. (Chemical Engineering Journal, 2026)

Speciation and light-absorbing properties of carbonaceous aerosols in a typical industrial city, Taiyuan, China - Ziyong Guo; Chenhui Li; Fengxian Liu; Ying Wei; Jiajie Li; Yanting Qiu; Taomou Zong; Ling Mu; Zhijun Wu; Jiancheng Wang (Atmospheric Environment, 2026)

A potent human neutralizing antibody targeting the receptor-binding site in the glycoprotein gp350 of Epstein-Barr virus - Qingtai Liang; Qian-Ying Zhu; Xin-Yan Fang; Jing Wei; Yi-En Xu; Yanan Zuo; Guo-Long Bu; Chu Xie; Sisi Shan; Cong Sun; Zheng Liu; Linqi Zhang; et al. (Science China Life Sciences, 2026)

Mobilizing farmer action for water pollution control: institutional trust and environmental concern in rural China - Lan Mu; Haoying Liu; Ying Li; Qiongyao Wang (Environment, Development and Sustainability, 2026)

Gestational dibutyl phthalate exposure impairs the ovarian reserve in offspring mice through METTL14-m6A-mediated PI3K-AKT-FOXO3a activation - Yan Zhang; Fuqing Yi; Ying He; Yidan Ma; Xinyi Mu; Yanqing Geng; Xin Yin; Rufei Gao; Liping Yan; Xuemei Chen; Junlin He (Journal of Hazardous Materials, 2026)

IgG release and peptides production by trypsin-driven selective hydrolysis of casein in bovine colostrum to improve immunomodulatory activity - Ying-Chao Qiu; Meng-Jiao Wang; Zi-Ying Zhao; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Bisphenol analogs affected hepatic development and disrupted lipid homeostasis in zebrafish larvae - Yao Zheng; Ying Huang; Jiajia Li; Liyan Teng; Yanyang Xu; Lilai Yuan; Wenbo Yang; Jing Qiu; Yongzhong Qian; Tingting Chai; Xiyan Mu (Environmental Pollution, 2026)

The Complete Mitochondrial Genome of a Newly Recorded Chinese Species of Diglyphus sabulosus (Hymenoptera: Eulophidae) and Insights into Its Phylogenetic Position - Lu-Chao Fang; Zhi-Qiang Ge; Ou-Yan Xi; Ze-Lu Mu; Hong-Ying Hu (Biochemical Genetics, 2026)

Germ layer specification and organotropism in lymphoma invasion - Yan Dong; Peng-Peng Xu; Xiao Han; Yu-Qing Wang; Yi Chen; Ying Fang; Yue Zhu; Qing Shi; Rong Shen; Zi-Yang Shi; Niu Qiao; Shu Cheng; et al. (Science Bulletin, 2026)

A novel antioxidant peptide DD12 (DWPDARGIWHND) derived from dry cured ham alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-ARE pathway - Ying-dao Nan; Si-qi Chen; Guan-hao Li; Ting-yu Li; Bai-de Mu; Juan Wang; Jian Feng; Hong-mei Li; Chun-xiang Piao (Food Research International, 2026)

Bioaccumulation and Elimination, and Risk Assessment of Diazepam in Carp (Cyprinus Carpio) - Zhen Yang; Xiaodong Xu; Ying Li; Xin Hu; Jinhua Xu; Lu Qiao; Huiwu Sun; Yingchun Mu (Bulletin of Environmental Contamination and Toxicology, 2026)

Adaptations in ancient oasis woodlands of the hyper-arid Tarim Basin, Northwestern China: charcoal and coprolite analyses - Kangkang Li; Konglan Shao; Ying Yang; Gill Plunkett; Robert Spengler; Bing Xu; Yong Wu; Xiaohong Tian; Dong Wei; Chunxue Wang; Huiqiu Shao; Guijin Mu; et al. (Archaeological and Anthropological Sciences, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Effect of CO2 and H2O on pyrolysis characteristics and structural evolution of Zhundong coal under rapid heating rate - Huanying Chi; Shichen Ding; Ying Zhao; Xiaoxuan Lyu; Yi Wang; Sheng Su; Song Hu; Jun Xiang; Qingsong Mu; Yanfei Li; Xian Fan; Hanjian Li (Fuel, 2026)

Mining allergens in Cryptotympana atrata nymphs: integrating proteomics and homology-based bioinformatics - Yuan He; Shu-tao Sun; Jian-bo Xiao; Qi-dong Ren; Ying-ying Chen; Meng-qi Zhang; Mu-xuan Wang; Xu Guo; Jin-yue Sun; Chao Liu (Food Chemistry, 2026)

Enhancing L-aspartate biosynthesis in Escherichia coli through combined pathway engineering and release of feedback inhibition - Daobin Wang; Tong Mu; Jingwen Yang; Xinran Ni; Xiyao Cheng; Jidong Liu; Ying Lin; Ning Li (Food Bioscience, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Rapid Visual Detection of Decapod Iridescent Virus 1 ( DIV1 ) by RPA Combined With LFS - Quanling Mu; Cunbao Ding; Ying Xie; Xi Zhen; Xianrui Wang; Tongaobo Qi; Jiaming Zhang; Yakun Yu (Journal of Fish Diseases, 2026)
Decapod iridescent virus 1 (DIV1) causes severe disease outbreaks in shrimp and crab culture areas. A simple, rapid, and visual DIV1 assay is important for the control of viral diseases. This study presented a novel DIV1 detection method that combines recombinase polymerase amplification (RPA) and lateral flow strip (LFS). After selecting primers and probes, we optimised the concentration of the reverse primers, reaction time, as well as reaction temperature of RPA‐LFS detection. RPA can amplify the target gene within 18 min at a constant temperature of 38°C, and LFS can observe the amplification results within 3 min. Importantly, there is no cross‐reactivity with other infectable shrimp viruses and pathogens, such as WSSV, IHHNV, TSV, EHP, CMNV, YHV, MrNV samples, as well as Vp AHPND . In addition, RPA‐LFS has high detection sensitivity, with a lower detection limit of 1.12 × 10 1 copies/μL. Using 110 field samples, the results of qPCR recommended by WOAH (OIE) and RPA‐LFS were identical, indicating that RPA‐LFS is as reliable as qPCR. The RPA‐LFS assay is a valuable tool for the rapid and accurate detection of DIV1.

Low-glutelin rice as a food-based strategy for protein restriction: Genetic development, structural engineering, and nutritional consequences - Ying Mei; Yuwei Hua; Yuxin Mu; Qiang Liu; Siqi Zhao; Xinbo Zhuang; Chao Ding; Liping Guo (Trends in Food Science & Technology, 2026)

Efficient recovery of high-purity 2D flaky R-FePO4 from lithium extraction slag leachate via solvent extraction and chemical precipitation - Haojie Mu; Lei Hu; Ying Sun; Yongping Liu (Journal of Cleaner Production, 2026)

Enzymatic hydrolysis of bovine casein assisted by microfluidization: Effects on functional properties and identification of anxiolytic peptides - Meng-Jiao Wang; Zi-Ying Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (International Dairy Journal, 2026)

Enhanced performances of iron-rich sludge ash for chemical looping gasification of pretreated rice straw by the modification of transition metal oxides - Ying Dai; Jinpeng Jiang; Xiran Xu; Meng Sun; Xiaoyuan Wang; Lin Mu; Jianbiao Chen; Yuezhao Zhu; Jinzhu Tan (Fuel, 2026)

Molecular insights into the microscopic promotion mechanism of CO2 hydrate formation by the natural amino acid L-methionine for hydrate-based CO2 sequestration - Yongcheng Luo; Zijian Zhang; Ya Li; Daoyi Chen; Ying Mu; Zhenyuan Yin (Fuel, 2026)

Sustained photodynamic antibacterial activity enabled by a robust CD-MOFs composite film via in-situ interfacial engineering for food preservation - Meiyan Li; Ying Shu; Shulai Liang; Yunping Zhu; Zhizhou Chen; Wenxiu Wang; Jianlou Mu; Jianfeng Sun; Qianyun Ma (Chemical Engineering Journal, 2026)

Dehydrocostus lactone induces apoptosis and mitophagy in gastric cancer cells through the ROS-mediated mitochondrial pathway - Qiuxiong Chen; Ying Li; Junjie Mu; Qian Ming; Chaohong Zhu; Ziyue He; Mengyue Ma; Xiaoqin Long; Hui Wu; Baoli Qiu; Lihe Zhang; Xian Yang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Seeds of Transformation: Assessing Farmers' Preferences and Intentions for Improving Agricultural Water‐Saving Irrigation Facilities - Lan Mu; Xuanwen Zeng; Chuanzhen Zhang; Renjie Ma; Ying Li; Qiongyao Wang (Irrigation and Drainage, 2026)
Promoting the enhancement of water‐saving irrigation facilities (WSIFs) within rural communities holds significant practical relevance in addressing agricultural water shortages. Utilizing survey data obtained from 495 farm households within the Wei River Basin in China, this study employs a choice experiment approach that incorporates the extended theory of planned behaviour (TPB) to investigate the willingness of farmers to advance WSIFs. The findings reveal a strong inclination among farmers towards WSIFs progression, with an average willingness‐to‐pay (WTP) of 2877.3 CNY per hectare per year. Significant heterogeneity in farmers' WSIFs preferences is evident, with a notable emphasis on land quality. Conversely, water quality, farmers' income and technical guidance/training have associated WTP values of 370.65, 697.05 and 699.6 CNY/ha/year, respectively. In our further TPB path analysis, factors such as attitudes, subjective norms, perceived behaviour control, knowledge and risk perception emerged as explanatory factors for farmers' intentions to transform their behaviour. Heterogeneity analysis indicates that those predominantly engaged in cash‐crop cultivation, actively utilizing WSIFs and exhibiting high TPB scores tend to display a heightened inclination towards WSIFs and higher WTP. The findings of this study may offer essential insights and feasible guidance for refining policies that promote WSIFs.

Beyond astaxanthin: The bioactive ingredients of Haematococcus pluvialis and their applications in food - Shu-tao Sun; Yan-jie Jiang; Jesus Simal-Gandara; Xu Guo; Shengxiang Yang; Ying-ying Chen; Meng-qi Zhang; Qi-dong Ren; Mu-xuan Wang; Jin-yue Sun; Ning-yang Li; Chao Liu (Trends in Food Science & Technology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Unveiling the black box: Multi-omics reveal how biochar supercharges synthetic biofilms for superior bioremediation - Bo Zhang; Xiaoying Hu; Lu Han; Zhen Guo; Yongqi Liu; Huiyao Li; Yuze He; Tianyu Liu; Qingyuan Pan; Yi Mu; Jianhua Qu; Hongqi Yu; et al. (Journal of Hazardous Materials, 2026)

Structural modulation of casein peptide-hydroxytyrosol self-assembled nanocomplexes: Enhanced gastrointestinal stability and in vitro antioxidant activity - Si-Yi Han; Hong-Fu Zhao; Wen-Qi Liang; Ying-Hua Zhang; Zhi-Shen Mu (Food Research International, 2026)

A multifunctional ion-conductive hydrogel with supramolecular interactions for wearable sensing: Human motion monitoring and Morse code communication - Ying Chen; Shenghua Lv; Leipeng Liu; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Microscopic probing into plasmodesmata (PD) and PD-derived intercellular gateways (PdIGs): Beyond morphology - Ming-fang Lv; Wei-na Shang; Yuan-xing Dai; Jun-ying Li; Yi Li; Shuai Fu; Jian Hong; Li Xie; Heng-Mu Zhang (Protoplasma, 2026)

Long Non-Coding RNA PVT1 Inhibits Apoptosis Through the miR-30d-5p/CaMKIIδ Axis in Hypoxic–Ischemic Brain Injury - Fengyan Zhao; Junyan Liu; Zihong Xiong; Lingyi Huang; Yuanyuan Zhao; Shiping Li; Junjie Ying; Qian Liu; Shaopu Wang; Xiaojuan Su; Jun Tang; Yi Qu; et al. (Molecular Neurobiology, 2026)

Discovery of novel nuciferine-based URAT1 inhibitors for hyperuricemia: synthesis, biological evaluation, and computational insights - Yan-fei Liu; Ze-sheng Hao; Xu Guo; Shu-tao Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Jin-yue Sun; Chao Liu (Medicinal Chemistry Research, 2026)

Acute effects of two different combined exercise modalities on executive function and circulating neurotrophic factors in young healthy adults - Yi-Hung Liao; Toby Mündel; Ying-Chu Chen; Shiow-Chwen Tsai; Kuo-Cheng Wu; Mu-Tsung Chen; Li-Chen Lee; Chih-Peng Su; Yu-Kai Chang; Chung-Yu Chen (European Journal of Applied Physiology, 2026)

A hybrid model driven by remotely-sensed data for simulating the impact of high spatiotemporal variations in fertilization and atmospheric N2O on N2O emissions in paddy fields - Wei Jiang; Xiang Gao; Housheng Wang; Xuerong Lang; Shuai Shen; Xian Hu; Linkai Wen; Qinchun Xu; Yan zhang; Xiaosan Jiang; Jinyang Wang; Yanfeng Ding; et al. (Agricultural and Forest Meteorology, 2026)

Incorporating spatiotemporal structure to improve the understanding of Antarctic krill (Euphausia superba) distribution - Xiuxia Mu; Xinliang Wang; Chongliang Zhang; Xianyong Zhao; Jichang Zhang; Yunxia Zhao; Yiping Ying; Gangzhou Fan; Lu Liu; Jiancheng Zhu; Qingchang Xu (Fisheries Research, 2025)

Unraveling humidity's dual effects on trace methane photocatalytic ozonation: Enhanced radical generation versus active site blockade - Junyu Ying; Yun Wang; Haiyuan Zhang; Yang Bai; Jiahua Zhu; Xiaohua Lu; Wei Li; Liwen Mu (Journal of Environmental Chemical Engineering, 2025)

Biodegradation of unpretreated polypropylene microplastic and agricultural polypropylene film by a bacterium isolated from an oil reservoir - Sheng Jin Li; Yun Yang Wan; Zhe Ke Zhong; Ying Jia Zhu; Hong Mei Mu; Sheng Bao Shi (Journal of Environmental Chemical Engineering, 2025)

Flexcube as an alternative aging vessel to the oak barrel: insights into flavor, oxygen, and matrix interactions - Dongsheng Cui; Yongce Huang; Mengqi Ling; Haibin Mu; Weiming Yang; Ying Shi; Changqing Duan; Mengyao Qi; Yibin Lan (Food Research International, 2025)

Uncovering the integrated metabolic profile of honey tea wine fermented by single and mixed yeast fermentation - Ying Li; Hexiang Qiu; Zhiwei Sun; Lanhua Liu; Yousheng Wang; Dongdong Mu; Xuefeng Wu; Xingjiang Li (Food Research International, 2025)

Demand-driven grafting engineering of IMC/PAM ionic conductive hydrogel: Multifunctional platforms for wearable sensors and TENGs - Ying Chen; Shenghua Lv; Tingxiang He; Jing Xu; Jinru Liu; Xiangyi Liu; Yanlu Mu; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

Study on the mechanism of costunolide inhibiting triple-negative breast cancer by EGFR ubiquitination and degradation to suppress the ERK/AKT signaling pathway - Ying Li; Junjie Mu; Qiuxiong Chen; Qian Ming; Chaohong Zhu; Yujie Xiao; Baoli Qiu; Xue Zhang; Baoshun Zhang; Xian Yang (Journal of Molecular Histology, 2025)

Impact of Foliar Application of Zinc Sulphate with Nitrogen Fertilizer on Morphological Responses and Yield Improvement of Winter Wheat (Triticum aestivum L.) - Riaz Ahmed; Junyi Mu; Jun Xing; Mehr Un Nisa; Yulai Zhang; Pengcheng Ding; Linghong Li; Ying You; Aixia Ren; Zhiqiang Gao; Min Sun (International Journal of Plant Production, 2025)

The landscape of decidual immune cells at the maternal–fetal interface in parturition and preterm birth - Mu Lv; Yuanhui Jia; Jiaqi Dong; Shengyu Wu; Hao Ying (Inflammation Research, 2025)

Towards sustainable separation of fuel additives - containing azeotrope by energy-saving extractive distillation process - Xiang Wang; Zhifan Chen; Jingyu Yu; Zhenlin Mu; Ying Xu; Yinglong Wang; Zhaoyou Zhu; Peizhe Cui; Guoxuan Li (Process Safety and Environmental Protection, 2025)

Effect of desalination-related pH shift on whey protein structure and digestion: Insights from spectroscopy, molecular dynamics simulation, and peptidomics - Meng-Qi Liu; Yun Chen; Hong-Fu Zhao; Ying-Chao Qiu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Preparation, characterization, and stability analysis of monascus red pigments water-in-oil emulsion - Shuang Wang; Weijia Yuan; Jun Liu; Jianfei Mu; Yongguang Guan; Yangchao Luo; Ying Liang (Food Chemistry, 2025)

Regulation of peptide hydrophobicity by self-assembly of casein peptides with ferulic acid to potentially reduce peptide bitterness and improve in vitro digestive activity - Si-Yi Han; Hong-Fu Zhao; Bo-Kang Yu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Investigating the variations in microbiome and volatilome characteristics of sauce-flavor Muqu across different grades and production rounds - Yu Mu; Linpei Liu; Junjun He; Hong Zhang; Shirui Yu; Zhiyu Zhu; Ying Huang; Mingyue Mou; Chunlin Zhang (Food Chemistry, 2025)

Emissions and carbon isotopic signatures of polycyclic aromatic compounds (PAHs, OPAHs) produced by coking in China - Jiajie Li; Ling Mu; Xiaofan Li; Xiaofeng Liu; Huiling Bai; Chuanyang Feng; Xin Jiang; Ying Wei; Chenhui Li (Environmental Pollution, 2025)

Construction of MXene/gelatin foam hydrogel with multi-stage porous for efficient solar-driven interfacial evaporation and ion removal - Jialong She; Shenghua Lv; Tingxiang He; Ying Chen; Yanlu Mu; Jinru Liu; Jing Xu; Xiangyi Liu; Leipeng Liu (Chemical Engineering Journal, 2025)

Astaxanthin ameliorates Cr (VI) accumulation, antioxidant, digestive, apoptosis and inflammatory response - Lei Zhao; Ying Zhang; Jie Yu; Yi-Han Liu; Zhi-Hao Cai; Mu-Yang Li; Ming Liu (Regional Studies in Marine Science, 2025)

Dual-functionalized MIL-53-NH₂ MOFs for high-capacity and reversible ammonia storage: Synergistic effects of hydrogen bonding and electrostatic interactions - Lei Zhang; Guifeng Xiang; Lei Zhang; Ruikang Song; Ying Wang; Yidan Mu; Ziqing Liu (Journal of Environmental Chemical Engineering, 2025)

Releasing ACE-inhibitory peptides from walnut protein via pulsed electric field: A multiscale mechanism-structure-function investigation - Xueying Song; Siliang Wu; Chenchen Cao; Yihan Mu; Ying Li; Ruili Liu; Guowan Su (Innovative Food Science & Emerging Technologies, 2025)

Microencapsulation of Acer truncatum seed oil using chickpea protein isolate–low/high-methoxy citrus pectin complex coacervates: Preparation, stability analysis, and application in milk - Mo Chen; Bo Zhang; Min Wang; Jin-yue Sun; Mu-xuan Wang; Meng-qi Zhang; Ying-ying Chen; Qi-dong Ren; Shu-tao Sun; Mohamed A. Farag; Xu Guo; Chao Liu (Food Hydrocolloids, 2025)

The vital role of current-topography interaction and tidal mixing in the upwelling around Zhoushan Archipelago - Jianshe Mu; Juncheng Xie; Peng Bai; Bo Li; Jingling Yang; Ying Gao (Continental Shelf Research, 2025)

Flexible and wearable strain sensor based on SSt/PAA/G composite hydrogel for human–machine interaction applications - Jinru Liu; Shenghua Lv; Yanlu Mu; Dequan Wei; Ying Chen; Tingxiang He; Jialong She; Leipeng Liu (Chemical Engineering Journal, 2025)

High-performance flexible porous pressure sensor based on carbon nanocoils modified reduced graphene oxide - Chunhong Mu; Ying Zhou; Yingzi Gu; Shengzhe Zhao (Chemical Engineering Journal, 2025)

Versatile, cost-effective and highly-multiplex nucleic acid detection through the Engineered Hairpin Cleavage Amplification (EHCA) strategy - Zhaocheng Liu; Rui Zhang; Yi Zhang; Huijun Mu; Xinyi Jiang; Jian Zou; Tingting Wang; Ying Yin (Chemical Engineering Journal, 2025)

HMGA2 Attenuates Tendon Stem/Progenitor Cell Senescence Via PI3K/AKT-Mediated Mitophagy Activation and SASP Suppression - Hao Wang; Guang-Chun Dai; Yu-Cheng Gao; Xiao-Yu Liu; Pan-Pan Lu; Mu-Min Cao; Ren-Wang Sheng; Liu Shi; Zhang Cheng; Ying-Juan Li; Yun-Feng Rui (Stem Cell Reviews and Reports, 2025)

Construction of a Machine Learning-Based Clopidogrel Resistance Risk Prediction Model - Ruo-Ying Wang; Shui-Di Yan; Jian-Qi Zeng; Tong Mu; Ya Yan; Yuan-Yi Zhao; Lin Xie; Li-Li Liu (Cardiovascular Toxicology, 2025)

Two novel 5,5-spiroketal sesquiterpenoid isomers from the roots of Angelica biserrata (R. H. Shan &Yuan) C. Q. Yuan & R. H. Shan - Fuyong Ni; Rongrong Li; Zixian Xie; Ying Li; Ningning Xu; Xuanyu Mu; Ming Yan; Chenfeng Zhang; Zhenzhong Wang; Xue Xie; Wei Xiao (Natural Product Research, 2025)

Short-chain chlorinated paraffins at environmentally relevant doses disrupt glucose homeostasis and insulin signaling by macrophage-mediated inflammation - Ying-Wen Mu; Wen-Huan Yao; Hui Li; Cui-Li Zhang; Yan-Jing Zhang; Xiu-Ning Zhang; Ge Song; Xiu-Lan Zhao; Tao Zeng (Journal of Hazardous Materials, 2025)

Structural evolution during processing of raw and refined coal tar pitch to mesophase pitch for needle coke - Yinda Wang; Wenqing Lv; Chunfeng Mu; Yuxin Wen; Dakui Zhang; Haifeng Liu; He Yang; Lijun Jin; Ying He; Haoquan Hu (Fuel, 2025)

Rosmarinic acid in Perilla frutescens L. as a potential adenosine deaminase inhibitor: Preparation, machine learning validation and binding mechanism study - Bo-hao Liu; Zhong-Han Li; Bao-rong Wang; Jie Zhou; Bing Zhang; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

Exploring Allium mongolicum Regel flavonoids alleviation of deoxynivalenol-induced gut inflammation and flesh-quality improvement based on muscle-intestinal axis in a Channa argus model - Zhe Yu; Zhuang Xiong; Yi Wang; Zhi-Qiang Gao; Ke-Xin Lu; Ying Zhang; Mu-Yang Li; Yuan-Xi Yue (Food Bioscience, 2025)

Unraveling the main chemical mechanism of PM2.5 pollution caused by open burning of sugarcane straw during winter in southern China: The Pivotal Role of NOx and NH3 Oxidation-Neutralization - Xu Wei; Guiyun Liang; Jingying Mao; Junchao Yang; Yijun Mu; Chuan Nong; Dabiao Zhang; Jiahui Lu; Xishou Huang; Ying Wu; Zhaoyu Mo (Environmental Pollution, 2025)

Hofmeister effect guided dual-crosslinked sodium alginate-based hydrogel with super-stretchable, self-adhesive, and antibacterial properties for flexible sensors in human activity monitoring - Tingxiang He; Shenghua Lv; Ying Chen; Yanlu Mu; Jinru Liu; Jialong She; Dequan Wei; Leipeng Liu (Chemical Engineering Journal, 2025)

Stage-specific responses of whitespotted conger (Conger myriaster) body condition to environmental variability and climate change - Xiuxia Mu; Chongliang Zhang; Yupeng Ji; Binduo Xu; Ying Xue; Yiping Ren (Hydrobiologia, 2025)

Environmental occurrence, human exposure routes, toxicity, and risk assessments of medium-chain chlorinated paraffins (MCCPs): a comprehensive review - Zhi-Hong Yu; Ying-Wen Mu; Yan-Chao Du; Tao Zeng (Archives of Toxicology, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Implementation or inaction: how governmental multi-interventions catalyze farmers' adoption for climate adaption technology? - Lan Mu; Ying Li; Haoying Liu; Qiongyao Wang (Journal of Cleaner Production, 2025)

Bone marrow microenvironment-targeted yolk-shell nanoparticle enhances acute myeloid leukemia chemotherapy by preventing endothelial cell/ECM-mediated adhesion - Shiyi Hong; Pei Peng; Yutian Huang; Siying Cai; Cao Yao; Tongtong Huang; Yulu Ying; Wei Li; Yang Xiong; Mancang Gu; Guilin Cheng; Chaofeng Mu (Chemical Engineering Journal, 2025)

Characteristics of loess landslides under the effects of faults and rivers and their correlations with geological and surficial evolutionary processes - Qi-qi Liu; Wan-li Xie; Hui Yang; Ming Yan; Rong-sen Zhu; Ke Mu; Yi-lun Chang; Shengjie Di; Xiaoliang He; Xiaomin Liu; Ying Zhang (Bulletin of Engineering Geology and the Environment, 2025)

Mixing mechanisms of hydrogen-blended natural gas in subsea pipelines: Effects of injection angles - Fenghui Han; Xichen Mu; Ying Wei; Wenhua Li; Zhe Wang (Ocean Engineering, 2025)

Fluoride enrichment in geothermal waters based on H, O, Sr, and Li isotopes of the Taiyuan Basin, North China - Chang Lu; Ying Li; Xiaocheng Zhou; Yuwen Wang; Weiye Shao; Zhaojun Zeng; Zhaofei Liu; Dawei Liao; Hui Zhang; Huimin Mu (Journal of Asian Earth Sciences, 2025)

Extraction of hydroxy safflower yellow A and anhydroxysafflor yellow B from safflower florets using natural deep eutectic solvents: Optimization, biological activity and molecular docking - Chun-Ying Wu; Bao-Rong Wang; Si-Yi Han; Ying-Hua Zhang; Zhi-Shen Mu (Food Bioscience, 2025)

Preparation and characterization of microcapsules for tuna oil by maillard reaction products of whey protein isolate and Arabic gum via complex coacervation - Kun-Long Wang; Bo-Kang Yu; Hong-Fu Zhao; Ye-Xuan Liu; Chun-Ying Wu; Ying-Hua Zhang; Zhi-Shen Mu (Food Chemistry, 2025)

A comb-shaped microfluidic aptasensor for rapid and sensitive on-site simultaneous detection of aflatoxin B1 and deoxynivalenol - Jinlei Wu; Haojun Yuan; Yunhua Yang; Ping Yang; Xinxin Yan; Ying Mu; Qinghui Jin; Panhui Yang; Wanlei Gao (Food Chemistry, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

Molecular characterization of a novel non-segmented double-stranded RNA mycovirus isolated from the phytopathogenic fungus Lasiodiplodia pseudotheobromae - Zhengzhe Guan; Mengjiao Wang; Jiayi Ma; Mengyuan Mu; Xinyu Li; Peimeng Sun; Mengyuan Zhang; Yuanyuan Zhang; Luyang Song; Caiyi Wen; Ying Zhao (Archives of Virology, 2025)

Potential effects of pH changes in the micro-environment during desalination on infant powder: The perspective of pH shift affecting whey protein molecular structure and function - Meng-Qi Liu; Wen-Xiu Zhi; Hong-Fu Zhao; Ying-Chao Qiu; Kun-Long Wang; Ying-Hua Zhang; Zhi-Shen Mu (Food Hydrocolloids, 2025)

Dynamic responses and adsorption mechanisms of Chlamydomonas reinhardtii extracellular polymeric substances under Cd, Cu, Pb, and Zn exposure - Chonghua Li; Peihuan Li; Hongxuan Fu; Zijian She; Chunhua Zhang; Yichun Li; Mu Zhang; Ying Ge (Environmental Pollution, 2025)

Unveiling the metabolic heterogeneity and formation mechanism in Chinese typical Daqu based on Qu-omics - Yu Mu; Shangjie Yao; Ying Huang; Zhiyu Zhu; Dong Li; Ya Song; Zehuan Liu; Chunlin Zhang; Shirui Yu (Food Research International, 2025)

The influence of polyphenols on the hydrolysis and formation of volatile esters in wines during aging: An insight of kinetic equilibrium reaction - Mengqi Ling; Dongsheng Cui; Baoqing Zhu; Demei Li; Haibin Mu; Jin Li; Ying Shi; Changqing Duan; Yibin Lan (Food Chemistry, 2025)

Effect of ambient ozone and its interactions with ambient PM2.5 and temperature on peak expiratory flow in adults with asthma - Dongxia Jiang; Ying Shang; Zhengxiong Li; Xianlin Mu; Xuehu Han; Xinzhuo Xie; Guanglong Fu; Yunshu Zhang; Shaodan Huang; Chun Chang (Atmospheric Environment, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Asymmetric synthesis of spiro[4H-chromene-3,3′-oxindoles] via a squaramide-organocatalytic three-component cascade Knoevenagel/Michael/cyclization sequence - Liming Wang; Hongwen Mu; Yuhong Sun; Ying Jin; Wei Zhang (Molecular Diversity, 2025)

Enhanced chemiluminescence by carbon dots for rapid detection of bisphenol A and nitrite - Yujie Xiao; Xiaoqin Long; Xue Zhang; Junjie Mu; Qiuxiong Chen; Yuxian Mai; Ying Li; Hao Xue; Pengyang Song; Xian Yang; Hong Zheng (Food Chemistry, 2025)

Changes in volatile flavors during the fermentation of tomato (Solanum lycopersicum L.) juice and its storage stabilization - Aihemaitijiang Aihaiti; Lei Zhao; Ruxianguli Maimaitiyiming; Liang Wang; Ruoqing Liu; Ying Mu; Keping Chen; Yu Wang (Food Chemistry, 2025)

Regulation of oxygen vacancy by in-situ piezoelectric synthesized BiVO4 to induce spin polarization for boosting the piezo-photocatalytic activity - Ying Cheng; Tao Yu; Xuefei Lei; Biao Wang; Wenning Mu; Xuanwen Liu; Rui Guo (Chemical Engineering Journal, 2025)

Digital one-pot SHERLOCK assisted superfast and reverse transcription free method for circulating microRNA absolute quantification - Zheyu Zou; Juxin Yin; Liping Xia; Weihong Yin; Ke Liu; Yating Pan; Kai Hu; Yehong Gui; Jianjian Zhuang; Duo Xiao; Ying Mu (Chemical Engineering Journal, 2025)

Construction of Al-doped FeCoP nanosheet array with superhydrophilic/superaerophobic characteristics as a bifunctional electrocatalyst for activating alkaline overall water splitting - Jinmei He; Yuqing Wang; Leihuan Mu; Jiehui Li; Yurou Dong; Ying Zhang; Yuan Deng; Pu Feng; Mengnan Qu (Journal of Water Process Engineering, 2024)

Combined application of multi-omics techniques and multivariate statistical analysis reveals the core functional microorganisms of Qula in Tibet, China - Ying Huang; Jiarong Li; Ting Li; Xingxing Deng; Qihong Zhong; Dezheng Wu; Zehuan Liu; Dawa Zhaxi; Yu Mu (Food Bioscience, 2024)

Isolation and Functional Analysis of Na+/H+ Antiporter Gene (LcNHX1) from Leymus chinensis - Chuanbo Sun; Chuang Zhang; Yuejia Yin; Ying Wang; Shujing Mu; Qing Liu; Ziyu Wang; Yang Liu; Chunxiao Zhang; Xiangguo Liu; Yan Zhang; Jia Guo (Plant Molecular Biology Reporter, 2024)

Mirids secrete a TOPLESS targeting protein to enhance JA-mediated defense and gossypol accumulation for antagonizing cotton bollworms on cotton plants - Yu-Pei Mu; Dian-Yang Chen; Yu-Jie Liu; Ming-Yu Zhu; Xian Zhang; Yin Tang; Jia-Ling Lin; Mu-Yang Wang; Xiao-Xia Shangguan; Xiao-Ya Chen; Chengshu Wang; Ying-Bo Mao (Molecular Plant, 2024)

Enhanced deep-water circulation facilitated rare earth elements enrichment in pelagic sediments from the northwestern Pacific Ocean - Dongjie Bi; Xuefa Shi; Mu Huang; Fangyu Shen; Miao Yu; Ying Zhang; Fengdeng Shi; Jihua Liu (Global and Planetary Change, 2024)

Transgenerational and parental impacts of acrylamide exposure on Caenorhabditis elegans: Physiological, behavioral, and genetic mechanisms - Yajuan Chen; Zihan Liu; Weijia Yuan; Shan Lu; Weidong Bai; Qinlu Lin; Jianfei Mu; Jianqiang Wang; Haifang Wang; Ying Liang (Environmental Pollution, 2024)

Preparation, structural properties, and in vitro and in vivo activities of peptides against dipeptidyl peptidase IV (DPP-IV) and α-glucosidase: a general review - Xinxin Mu; Rongchun Wang; Cuilin Cheng; Ying Ma; Yingchun Zhang; Weihong Lu (Critical Reviews in Food Science and Nutrition, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

Use of Tirofiban to Prevent Ischemic Events in Patients with CYP2C19 Loss-of-Function Alleles during Flow Diversion of Intracranial Aneurysm: A Multicenter Cohort Study - Yangyang Zhou; Huibin Kang; Wenqiang Li; Bin Luo; Chao Wang; Ruhang Xie; Yongnan Zhu; Qichen Peng; Yisen Zhang; Jian Liu; Ying Zhang; Shiqing Mu; et al. (Translational Stroke Research, 2024)

Multi-objective optimization of clean utilization for zinc leaching residues by rotary kiln using neural network coupled modeling - Chen-Mu Zhang; Zhi Zan; Yao Shi; Hui-Quan Li; Lang-Ming Liu; Wei-Ping Liu; Wen-Jun Lin; Jing-Jing Shi; Ying-yan Hu; Xue Guan; Kuang-Yi Chen; Xiao Liu; et al. (Journal of Cleaner Production, 2024)

Revealing the comprehensive effect of mechanization on sauce-flavor Daqu through high-throughput sequencing and multi-dimensional metabolite profiling - Yu Mu; Ying Huang; Dong Li; Zhiyu Zhu; Shirui Yu; Feng Xie (Food Research International, 2024)

Dimeric piperidinoquinoline alkaloids from the seeds of Chimonanthus salicifolius - Zhan-Peng Yu; Yu-Xia Wang; Li-Hong Hong; Ya-Lin Li; Jian-Fei Zhang; Mu Li; Ping Ying; Qiang Zheng; Ling-Yi Kong; Jian-Guang Luo (Phytochemistry Letters, 2024)

Effect of plasma on ochratoxin degradation and raisin properties - Ying Wang; Yu Zheng; Jianjun Wang; Longtao Mu; Wenting Zhang; Mengting Huang; Yining Li (Journal of Food Engineering, 2024)

An inclusive study to elucidation the heavy metals-derived ecological risk nexus with antibiotic resistome functional shape of niche microbial community and their carbon substrate utilization ability in serpentine soil - Suprokash Koner; Jung-Sheng Chen; Zeng-Yei Hseu; Ed-Haun Chang; Kuang-Ying Chen; Aslia Asif; Bing-Mu Hsu (Journal of Environmental Management, 2024)

Development of an ELISA method to determine adulterated cow milk in camel milk - Shi-Xin Chi; Bo-Hao Liu; Bing Zhang; Bao-Rong Wang; Jie Zhou; Ling Li; Ying-Hua Zhang; Zhi-shen Mu (International Dairy Journal, 2024)

Dynamic mechanism of CO2 capture from flue gas via hydrate-based method induced by using IB group transition metal functionalized carbon nanotubes - Fang Wang; Wenjing Lin; Jinchi Mu; Xiaosheng An; Ruiyang Zhang; Lihong Guo; Ying Zhou (Gas Science and Engineering, 2024)

Combining lipase enzymatic techniques and antioxidants on the flavor of structured lipids (SLs) prepared from goat butter and coconut oil - Weihao Mu; Ying Zhao; Zhuo Wang; Yajun He; Chen Yang; Jianming Wang (Food Bioscience, 2024)

Novel insights into whey protein peptide-iron chelating agents: Structural characterization, in vitro stability and functional properties - Yumei Wu; Ying Wang; Zezhen Ma; Guangqing Mu; Fang Qian (Food Bioscience, 2024)

Circ-IP6K2 suppresses tumor progression by modulating the miR-1292-5p/CAMK2N1 signal in clear cell renal cell carcinoma - Jian-ying Tang; Lu Yang; Qing-Jian Wu; Ying Yang; Yuan-Yuan Su; Yi-Rong Chen; Jiao Mu (Functional & Integrative Genomics, 2024)

Distribution, risk evaluation, and source allocation of cesium and strontium in surface soil in a mining city - Jia-li Li; Chun-dan Gan; Xin-yue Du; Xue-ying Yuan; Wen-lin Zhong; Meng-qi Yang; Rui Liu; Xiao-yu Li; Hao Wang; Yu-liang Liao; Zheng Wang; Mu-cheng Xu; et al. (Environmental Geochemistry and Health, 2024)

A Data Driven Strategy and Case Study for Implementation of Singlicate Analysis in Ligand Binding Assays Used for PK Quantitation - Qiang Qu; Susana Liu; Zhiping You; Gregory S. Steeno; Lisa A. Dyleski; Xue Mu; Ying Wang; Daniel Baltrukonis (The AAPS Journal, 2024)

Exploring the novel antioxidant peptides in low-salt dry-cured ham: Preparation, purification, identification and molecular docking - Ying-dao Nan; Bai-de Mu; Chang-xin Ge; Si-qi Chen; Ming-xun Cui; Hong-mei Li; Chang-cheng Zhao; Juan Wang; Chun-xiang Piao; Guan-hao Li (Food Chemistry, 2024)

The construction of Cs3MoxSbyBr9/BiVO4 S-scheme heterojunction photocatalyst for efficient photocatalytic N2 fixation - Zhao-Lei Liu; Han-Ying Luo; Meng-Ran Zhang; Yan-Fei Mu; Fu-Quan Bai; Min Zhang; Tong-Bu Lu (Chemical Engineering Journal, 2024)

Characterization of cotinine degradation in a newly isolated Gram-negative strain Pseudomonas sp. JH-2 - Kexin Wang; Lu Xu; Jiale Ma; Ying Zhou; Yinhu Jiang; Jie Zha; Yanqiu Cai; Jian He; Jiandong Jiang; Jiguo Qiu; Yang Mu (Archives of Microbiology, 2024)

Upcycling crab shell waste into biochar for treatment of palm oil mill effluent via microwave pyrolysis and activation - Yan Yang; Shin Ying Foong; Yifeng He; Rock Keey Liew; Nyuk Ling Ma; Peter Nai Yuh Yek; Shengbo Ge; Mu. Naushad; Su Shiung Lam (Environmental Research, 2024)

Non-targeted metabolomics identifies biomarkers in milk with high and low milk fat percentage - Xiaofang Feng; Ruoshuang Ma; Ying Wang; Lijia Tong; Wan Wen; Tong Mu; Jia Tian; Baojun Yu; Yaling Gu; Juan Zhang (Food Research International, 2024)

Construction of and evaluation of the immune response to two recombinant pseudorabies viruses expressing the B119L and EP364R proteins of African swine fever virus - Xin-Mei Geng; Ying-Mu Xi; Xiang-Mei Huang; Yang-Lin Wang; Xu-Ying Wang; Kang Ouyang; Ying Chen; Zu-Zhang Wei; Yi-Feng Qin; Wei-Jian Huang (Archives of Virology, 2024)

Foraging flight-based health indicators for honey bee colonies using automatic monitoring systems - Joe-Air Jiang; Jen-Cheng Wang; Chien-Peng Huang; Mu-Hwa Lee; An-Chi Liu; Hung-Jen Lin; Chien-Hao Wang; Cheng-Ying Chou; En-Cheng Yang (Computers and Electronics in Agriculture, 2024)

Occurrence of polyhalogenated carbazoles and the combined effects with heavy metals on variation in bacterial communities in estuarine sediments - Shanmin Hu; Minggang Zheng; Yingdi Mu; Aifeng Liu; Yuqing Jiang; Ying Li; Ke Ning; Ling Wang (Marine Pollution Bulletin, 2024)

Effects of bubble and reactor shape on cold plasma yeast inactivation - Ying Wang; Guanting Pan; Yining Li; Longtao Mu; Mingwei Zhao; Yu Zheng (Journal of Food Engineering, 2024)

Exploring the heterogeneity of community and function and correspondence of “species-enzymes” among three types of Daqu with different fermentation peak-temperature via high-throughput sequencing and metagenomics - Ying Huang; Dong Li; Yu Mu; Zhiyu Zhu; Yuzhang Wu; Qi Qi; Yingchun Mu; Wei Su (Food Research International, 2024)

Aerogel-based solar interface evaporation: Current research progress and future challenges - Jiehui Li; Qinghua Liu; Jinmei He; Ying Zhang; Leihuan Mu; Xuedan Zhu; Yali Yao; Cai-Li Sun; Mengnan Qu (Desalination, 2024)

Chemerin/CMKLR1 pathway exacerbates cisplatin-induced spiral ganglion neuron injury - Jie Tian; Ying Mu; Lili Ma (Toxicological Research, 2024)

Characterization and fine mapping of a maize lesion mimic mutant (Les8) with enhanced resistance to Curvularia leaf spot and southern leaf blight - Jiankun Li; Tianyuan Fan; Ying Zhang; Ye Xing; Mengyao Chen; Ying Wang; Jie Gao; Na Zhang; Jinjun Tian; Chenyang Zhao; Sihan Zhen; Junjie Fu; et al. (Theoretical and Applied Genetics, 2024)

An update on the effects of food-derived active peptides on the intestinal microecology - Jianfei Mu; Qinlu Lin; Ying Liang (Critical Reviews in Food Science and Nutrition, 2023)

Inoculum size-insensitive susceptibility determination of urine sample based on in-situ measurement of inducible enzyme activity after 20 min of antibiotic exposure - Wenshuai Wu; Yuanjie Suo; Qianbin Zhao; Gaozhe Cai; Yang Liu; Wei Jin; Ying Mu; Boran Zhang (Analytica Chimica Acta, 2023)

The regulative effect and repercussion of probiotics and prebiotics on osteoporosis: involvement of brain-gut-bone axis - Yuan-Wei Zhang; Mu-Min Cao; Ying-Juan Li; Guang-Chun Dai; Pan-Pan Lu; Ming Zhang; Li-Yong Bai; Xiang-Xu Chen; Cheng Zhang; Liu Shi; Yun-Feng Rui (Critical Reviews in Food Science and Nutrition, 2023)

Towards low energy-carbon footprint: Current versus potential P recovery paths in domestic wastewater treatment plants - Qian Zhao; Hao Ying; Yu Liu; Hongbo Wang; Jingtao Xu; Wei Wang; Juan Ren; Shujuan Meng; Ning Wang; Ruimin Mu; Shasha Wang; Jingjing Li (Journal of Environmental Management, 2023)

Chromones from the whole plant of Hypericum elodeoides and their bioactivities - Yanbing Mu; Letian Cui; Ping Ying; Huiping Wen; Dujuan Zhan; Lingyi Kong; Jun Luo (Phytochemistry Letters, 2023)

Transcriptomic analysis of the fat body of resistant and susceptible silkworm strains, Bombyx mori (Lepidoptera), after oral treatment with fenpropathrin - Zi-qin Zhao; Kai-yi Zheng; Yu-tong Zhu; Jun-li Lv; Zhi-hao Su; Xiao-ying Zhang; Wen-qing Lai; Mu-wang Li; Yang-chun Wu; Xue-yang Wang (Pesticide Biochemistry and Physiology, 2023)

Composition and transcriptional activity of oil reservoir microorganisms under different gas/liquid ratios - Li-Bin Shou; Zhao-Wei Hou; Yi-Fan Liu; Ying Wang; Lei Zhou; Jin-Feng Liu; Shi-Zhong Yang; Ji-Dong Gu; Xiao-Lin Wu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2023)

Identification of sweet spots in shale-type and siltstone-type “shale oil systems”: A case study of the Chang 7 Member in Ordos Basin - Songqi Pan; Qiulei Guo; Caineng Zou; Zhenhua Jing; Ming Yuan; Ying He; He Zheng; Ying Mu; Zhi Yang; Shixiang Li; Xinping Zhou; Songtao Wu; et al. (Science China Earth Sciences, 2023)

Short-term effects of individual exposure to PM2.5 on hospital admissions for myocardial infarction and stroke: a population-based case-crossover study in Guangzhou, China - Jie-Qi Jin; Guo-Zhen Lin; Shuang-Ying Wu; Mu-Rui Zheng; Hui Liu; Xiang-Yi Liu; Min-Qian Yan; Zhao-Yue Chen; Chun-Quan Ou (Environmental Science and Pollution Research, 2023)

Membrane with horizontally rigid zeolite nanosheet arrays against zinc dendrites in zinc-based flow battery - Yongsheng Xia; Xiaoxuan Hou; Xinyi Chen; Feiyan Mu; Yan Wang; Liheng Dai; Xin Liu; Ying Yu; Kang Huang; Weihong Xing; Zhi Xu (Chemical Engineering Journal, 2023)

The potential health risks of short-chain chlorinated paraffin: A mini-review from a toxicological perspective - Ying-Wen Mu; Dong Cheng; Cui-Li Zhang; Xiu-Lan Zhao; Tao Zeng (Science of The Total Environment, 2023)

5-epi-ent-Kaurane diterpenoids from the aerial parts of Isodon eriocalyx and their anti-atherosclerotic potential - Long Mu; Tian Li; Peng-Lin Wu; Ling-Qiao Cai; Shu-Ying Li; Zi-Yuan Wang; Yuan-Yuan Liu; Jie Wang; Dong Yan; Zheng-Yun Rao; Chao-Jun Wang; Jian Zhang; et al. (Phytochemistry, 2023)

Analysis of oil synthesis pathway in Cyperus esculentus tubers and identification of oleosin and caleosin genes - Youcheng Zhu; Ying Wang; Zunmiao Wei; Xiaokai Zhang; Bingyang Jiao; Yu Tian; Fan Yan; Jingwen Li; Yajing Liu; Xuguang Yang; Jinhao Zhang; Xinyue Wang; et al. (Journal of Plant Physiology, 2023)

Targeting Senescent Tendon Stem/Progenitor Cells to Prevent or Treat Age-Related Tendon Disorders - Hao Wang; Guang-Chun Dai; Ying-Juan Li; Min-Hao Chen; Pan-Pan Lu; Yuan-Wei Zhang; Ming -Zhang; Mu-Min Cao; Yun-Feng Rui (Stem Cell Reviews and Reports, 2023)

Ecological carrying capacity and carbon sequestration potential of bivalve shellfish in marine ranching: A case study in Bohai Bay, China - Zepeng Li; Yan Chen; Gang Wang; Jiandong Mu; Yanfeng Sun; Haolin Yu; Jiangling Xu; Ying Yan; Shuangyue Luo; Fuqiang Han; Jie Feng; Zhe Pan (Frontiers in Marine Science, 2023)
Introduction Shellfish play an important role in ecological restoration and as carbon (C) sinks, but studies on their ecological carrying capacity (ECC) and C sequestration potential are sparse. Methods In this study, we selected a 57-hectare artificial oyster reef in a typical marine ranching in Bohai Bay, China, to evaluate the ECC and their C sequestration potential of bivalve shellfish, and projecting their impact on functional groups in the system, with an Ecopath with Ecosim (EwE) food web model. We conducted four biological surveys to obtain the biomass measurements, with one conducted in each of the summer, autumn, and winter of 2019 and one in the spring of 2020; and the functional groups included in the surveys comprised fish, cephalopods, crustaceans, snails, bivalve shellfish, annelids, other macrobenthos, meiobenthos, starfish, sea cucumbers, zooplankton, phytoplankton, and detritus. Results and Discussion The EwE model prediction results showed that the ECC of bivalve shellfish was established to be 282.66 t/km 2 , far more than the existing quantity of 187.76 t/km 2 . Therefore, at present, the ecosystem of the study marine ranching is not yet mature. Moreover, our ecological network analysis parameters indicated that the marine ranching ecosystem will be mature and stable when the bivalve shellfish population reaches its ECC. However, the increase in bivalve shellfish biomass will result in a decrease in the population sizes of species competing for food resources with bivalve shellfish, mainly gobiid fish such as Tridentiger bifasciatus, Tridentiger trigonocephalus, Tridentiger barbatus . Simultaneously, when the bivalve shellfish reach their ECC, 29.23 t of CO 2 can be sequestrated by bivalve shellfish, comprising 14.32 t being removed from the ecosystem as prey and 14.91 t being stored on the seafloor through biodeposition. Conclusion Therefore, the research demonstrated that, within the scope of ECC, the increasing bivalve shellfish can improve the C sequestration capacity of the marine ranch ecosystem, and effective management of bivalve shellfish in marine ranching can improve the economic benefits and C sink service functions of marine ranching.

Chemical contaminants from food contact materials and articles made from or containing wood and bamboo – a review - Mu-Ying Guan; Huai-Ning Zhong; Zhi-Wei Wang; Wen-Wen Yu; Chang-Ying Hu (Food Additives & Contaminants: Part A, 2023)

Chemical speciation and bioavailability of potentially toxic elements in surface sediment from the Huaihe River, Anhui Province, China - Mu You; Yunhu Hu; Ying Meng (Marine Pollution Bulletin, 2023)

Combined Effects of Biochar-Sedum plumbizincicola on Cadmium Concentration in Cd-Contaminated Limestone Soil and Cadmium Absorption in Lactuca sativa - Ying-Ying Liu; Wen-Min Luo; Gui-Ting Mu; Xian-Liang Wu; Zhen-Ming Zhang (Water, Air, & Soil Pollution, 2023)

The Prevention Effect of Bacillus subtilis on Escherichia coli–Induced Mastitis in Mice by Suppressing the NF-κB and MAPK Signaling Pathways - Xiaoyu Hu; Ruibo Tang; Caijun Zhao; Ruiying Mu; Ying Wang; Yongguo Cao; Naisheng Zhang; Yunhe Fu (Probiotics and Antimicrobial Proteins, 2023)

Construction of novel Heat-conducting Cu-based MOF nanocomposite (HK-mBNNS/PVDF) film for highly efficient Ad-/desorption of toluene - Junjie Li; Liming Liu; Syed Jalil Shah; Ying Tang; Shanliang Jiang; Guangyuan Mu; Quanru Man; Zhongxing Zhao; Zhenxia Zhao (Chemical Engineering Journal, 2023)

Neural Mechanism Underlying Task-Specific Enhancement of Motor Learning by Concurrent Transcranial Direct Current Stimulation - Ying Wang; Jixian Wang; Qing-Fang Zhang; Ke-Wei Xiao; Liang Wang; Qing-Ping Yu; Qing Xie; Mu-Ming Poo; Yunqing Wen (Neuroscience Bulletin, 2023)

Environmental impact of typical zinc smelting that implements solid waste collaborative utilization in China - Wei-Ning Liu; Yao Shi; Chen-Mu Zhang; Lang-Ming Liu; Hui-Quan Li; Bin Lu; Yuan-Bo Xie; Cai-Bei Zhuang; Tian-You Sun; Wei-Ping Liu; Xue Guan; Ying-Yan Hu (The International Journal of Life Cycle Assessment, 2022)

An association study on the risk, glucocorticoids effectiveness, and prognosis of systemic lupus erythematosus: insight from mitochondrial DNA copy number - Zhen Li; Qi-Qun Zong; Chun-Xia Zhai; Guang-Hui Yu; Wan-Qin Hu; Yu-Hua Wang; Lin-Lin Wang; Zi-Ye Yan; Ting-Yu Zhang; Ying Teng; Shuang Liu; Jing Cai; et al. (Immunologic Research, 2022)

Integrated toxicity assessment of DEHP and DBP toward aquatic ecosystem based on multiple trophic model assays - Lilai Yuan; Jia Liu; Ying Huang; Gongming Shen; Sen Pang; Chengju Wang; Yingren Li; Xiyan Mu (Environmental Science and Pollution Research, 2022)

Hepatocyte steatosis inhibits hepatitis B virus secretion via induction of endoplasmic reticulum stress - Qichuang Liu; Maoyuan Mu; Huan Chen; Guoyuan Zhang; Yanqing Yang; Jun Chu; Ying Li; Fangwan Yang; Shide Lin (Molecular and Cellular Biochemistry, 2022)

Checking transformation efficiency for different Lagenaria siceraria genotypes by using seed germination pouches as a growth carrier - Ying Wang; Lijuan Huang; Yanwei Li; Zishan Feng; Zihan Mu; Jian Wang; Xinyi Wu; Baogen Wang; Zhongfu Lu; Guojing Li; Xiaohua Wu (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)
Bottle gourd [ Lagenaria siceraria (Mol.) Standl.] is one of the most common horticultural and medicinal crops. Genetic transformation is a rate-limiting step in unraveling the function of genes and molecular breeding in this non-model crop. In this study, we established an optimized protocol for transformation using a seed germination pouch as a growth carrier and developed bottle gourd composite plants. Overground explants were inoculated with Agrobacterium rhizogenes strain R1000, which harbored a binary vector pBI121 carrying the GUS reporter gene. The integration of GUS into transgenic roots was confirmed via reverse transcription-polymerase chain reaction and histochemical staining. Furthermore, we screened for desirable genotypes from 14 bottle gourd germplasm collections based on the number of induced roots, transformation efficiency, and induction rate, and “Changguang” (transformation efficiency, approximately 36.8%) was selected as the genotype suitable for hairy root induction in bottle gourd. The optimized protocol presented here is a rapid, suitable, and efficient tool for studying the function of genes and root biology of bottle gourd in the future.

Assessing the effectiveness and function of the water resources tax policy pilot in China - Rulin Ouyang; Enlin Mu; Yibin Yu; Ying Chen; Jiangbo Hu; Haoran Tong; Zhe Cheng (Environment, Development and Sustainability, 2022)

Synthetic lethality in personalized cancer therapy - Ying Pang; Meng Cheng; Mu Chen; Kaijun Zhao; Yuanyuan Yin; Min Liu; Jing Zhang; Chunlong Zhong (Genome Instability & Disease, 2022)

Linkages among the functional traits, insect visitation rate and seed set of Gentiana taxa on the Tibetan Plateau - Wen-fei Dai; Rui Gao; Meng-ying He; Yu-lian Yang; Fang-lan Li; Jun-peng Mu (Journal of Mountain Science, 2022)

Several major issues concerning the environmental transmission and risk prevention of SARS-CoV-2 - Jin Ma; Jian Xu; Xiaoli Zhao; Shouliang Huo; Xiaoli Duan; Yunsong Mu; Ying Wang; Yuan Wei; Jiang Chang; Xiaowei Jin; Fengchang Wu (Science China Earth Sciences, 2022)

The IAMAS-CNC Early Career Scientists Nobel Prize Online Interpretation Workshop - Jing Li; Zhongjing Jiang; Yueming Dong; Lu Zhang; Tong Ying; Zhenyu Zhang; Mu Mu (Advances in Atmospheric Sciences, 2022)

Toxicity and behavioral response of zebrafish exposed to combined microplastic and bisphenol analogues - Xiyan Mu; Suzhen Qi; Jia Liu; Lilai Yuan; Ying Huang; Jiaying Xue; Le Qian; Chengju Wang; Yingren Li (Environmental Chemistry Letters, 2022)

Historical Connectivity and Demography of the Ferocious Reef Crab, Eriphia ferox (Crustacea; Eriphiidae), Demonstrate That Taoyuan Algal Reef Is an Essential Population Source Along the East Taiwan Strait - Mu-Han Chen; Ya-Yi Huang; Bi-Ying Huang; Hernyi Justin Hsieh; Jen Nie Lee; Mei Lin Neo; Hironobu Fukami; Chaolun Allen Chen (Frontiers in Marine Science, 2022)
The east Taiwan Strait is largely fringed by sandy and muddy habitats. However, a massive algal reef made of crustose coralline algae has been found along the coast off Taoyuan city in northwestern Taiwan. The porous structure of Taoyuan Algal Reef harbors high abundance and diversity in marine organisms, including the ferocious reef crab, Eriphia ferox . Such a pivotal geographic location and unique ecological features make Taoyuan Algal Reef a potential stepping stone connecting biotic reefs in the east Taiwan Strait, South China Sea to the south, and even the high latitude of Japan to the north. In this study, we examined the population connectivity and historical demography of E. ferox by analyzing mitochondrial cytochrome oxidase I (COI) fragments of 317 individuals sampled from 21 localities in the northwestern Pacific. Our analyses of haplotype network and pairwise F ST comparisons revealed a lack of phylogeographical structure among E. ferox populations, implying the existence of a migration corridor connecting the South and East China Seas through the east Taiwan Strait. Multiple lines of evidence, including significant values in neutrality tests, unimodally shaped mismatch distributions, and Bayesian skyline plots elucidated the rapid population growth of E. ferox following the sea-level rise after Last Glacial Maximum (ca. 2–10 Ka). Such demographic expansion in E. ferox coincided with the time when Taoyuan Algal Reef started to build up around 7,500 years ago. Coalescent migration analyses further indicated that the large and continuous E. ferox population exclusively found in Datan Algal Reef, the heart of Taoyuan Algal Reef, was a source population exporting migrants both northward and southward to the adjacent populations. The bidirectional gene flow should be attributed to larval dispersal by ocean currents and secondary contact due to historical population expansion. Instead of serving as a stepping stone, our results support that Taoyuan Algal Reef is an essential population source for biotic reef-associated species along the east Taiwan Strait, and highlight the importance of conserving such a unique ecosystem currently threatened by anthropogenic development.

Varying growth rates of a marine eel, the whitespotted conger (Conger myriaster), are explained by the interaction between seasonal temperature and prey availability - Xiuxia Mu; Chongliang Zhang; Binduo Xu; Yupeng Ji; Ying Xue; Yiping Ren (Marine Biology, 2022)

Transient silencing of VvCSN5 enhances powdery mildew resistance in grapevine (Vitis vinifera) - Kai-Cheng Cui; Min Liu; Gui-Hua Ke; Xing-Yuan Zhang; Bo Mu; Min Zhou; Yang Hu; Ying-Qiang Wen (Plant Cell, Tissue and Organ Culture (PCTOC), 2021)

Unsymmetric compressibility matrix to model P-wave attenuation - Guangquan Li; Ying Mu; Chaodi Xie (Acta Geodaetica et Geophysica, 2021)

Synchronized research on endothelial dysfunction and microcirculation structure in dorsal skin of rats with type 2 diabetes mellitus - Yajie Wei; Huimin Chen; Qingzhuo Chi; Ying He; Lizhong Mu; Chao Liu; Yunxia Lu (Medical & Biological Engineering & Computing, 2021)

Genome analysis of Salmonella phage vB_SalM_8-19 (genus Rosemountvirus) - Cong Cong; Wei Bing Dong; Cui Hui Jing; Yuan Yu Yu; Xu Yong Ping; Wang Li Li; Li Shu Ying; Li Ji Bin; Xu Mu; Li Xiao Yu (Archives of Microbiology, 2021)

Correction to: A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

A Brush–Spin–Coating Method for Fabricating In Vitro Patient-Specific Vascular Models by Coupling 3D-Printing - Qing-Zhuo Chi; Li-Zhong Mu; Ying He; Yong Luan; Yu-Chen Jing (Cardiovascular Engineering and Technology, 2021)

Myosin18B predicts favorable prognosis of cutaneous squamous-cell carcinoma - Can Cao; Chao Zhang; Ying Sun; Zhen Mu; Qin Shen (Genes & Genomics, 2021)

Human growth hormone proteoform pattern changes in pituitary adenomas: Potential biomarkers for 3P medical approaches - Biao Li; Xiaowei Wang; Chenguang Yang; Siqi Wen; Jiajia Li; Na Li; Ying Long; Yun Mu; Jianping Liu; Qin Liu; Xuejun Li; Dominic M. Desiderio; et al. (EPMA Journal, 2021)

Use of QSAR and SSD methods on deriving predicted no-effect concentrations in seawater and sediment for ten individual parent- and alkyl-PAHs and a case study on the assessment of their ecological risks from the Dalian Bay, China - Ying Wang; Xing Liu; Yi Cong; Jin Fei; Juying Wang; Dian Zhang; Liang Liu; Jingli Mu; Ziwei Yao (Acta Oceanologica Sinica, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

A new indole alkaloid with anti-inflammatory from the branches of Nauclea officinalis - Le-Ling Song; Yan-Ling Mu; Hao-Chao Zhang; Gui-Ying Wu; Jing-Yong Sun (Natural Product Research, 2020)

New land use regression model to estimate atmospheric temperature and heat island intensity in Taiwan - Chin-Yu Hsu; Uen-Ching Ng; Chiao-Ying Chen; Yu-Cheng Chen; Mu-Jean Chen; Nai-Tzu Chen; Shih-Chun Candice Lung; Huey-Jen Su; Chih-Da Wu (Theoretical and Applied Climatology, 2020)

Using β-ocimene to increase the artemisinin content in juvenile plants of Artemisia annua L. - Mu Xiao; Rong Liu; Chenfeng Long; Ying Ruan; Chunlin Liu (Biotechnology Letters, 2020)

Identification and characterization of the Bacillus atrophaeus strain J-1 as biological agent of apple ring rot disease - Yangping Mu; Ying Yue; Guirong Gu; Yiming Deng; Hong Jin; Ke Tao (Journal of Plant Diseases and Protection, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Decreased mRNA Expressions of CD40L in Patients with Neuromyelitis Optica Spectrum Disorder - Ziyan Shi; Ling Feng; Zhiyun Lian; Ju Liu; Hongxi Chen; Qin Du; Ying Zhang; Qin Zhang; Mu Yang; Hongyu Zhou (Journal of Molecular Neuroscience, 2020)

Contrasting the Pb (II) and Cd (II) tolerance of Enterobacter sp. via its cellular stress responses - Zhongquan Jiang; Liu Jiang; Lin Zhang; Mu Su; Da Tian; Tong Wang; Yalin Sun; Ying Nong; Shuijin Hu; Shimei Wang; Zhen Li (Environmental Microbiology, 2020)
Summary Successful application of microorganisms to heavy metal remediation depends on their resistance to toxic metals. This study contrasted the differences of tolerant mechanisms between Pb 2+ and Cd 2+ in Enterobacter sp. Microbial respiration and production of formic acid showed that Enterobacter sp. had a higher tolerant concentration of Pb (>1000 mg l −1 ) than Cd (about 200 mg l −1 ). Additionally, SEM confirmed that most of Pb and Cd nanoparticles (NPs) were adsorbed onto cell membrane. The Cd stress, even at low concentration (50 mg l −1 ), significantly enlarged the sizes of cells. The cellular size raised from 0.4 × 1.0 to 0.9 × 1.6 μm on average, inducing a platelet‐like shape. In contrast, Pb cations did not stimulate such enlargement even up to 1000 mg l −1 . Moreover, Cd NPs were adsorbed homogeneously by almost all the bacterial cells under TEM. However, only a few cells work as ‘hot spots’ on the sorption of Pb NPs. The heterogeneous sorption might result from a ‘self‐sacrifice’ mechanism, i.e., some cells at a special life stage contributed mostly to Pb sorption. This mechanism, together with the lower mobility of Pb cations, caused higher microbial tolerance and removal efficiency towards Pb 2+ . This study sheds evident contrasts of bacterial resistance to the two most common heavy metals.

Impacts of replacement of dietary fish oil by vegetable oils on growth performance, anti-oxidative capacity, and inflammatory response in large yellow croaker Larimichthys crocea - Hua Mu; Chaoqing Wei; Yanjiao Zhang; Huihui Zhou; Ying Pan; Jia Chen; Wenbing Zhang; Kangsen Mai (Fish Physiology and Biochemistry, 2020)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

TLC-bioautography directed isolation of antibacterial compounds from active fractionation of Ferula ferulioides - Zhong-Lin Sun; Tao Liu; Shuang-Ying Wang; Xiao-Yue Ji; Qing Mu (Natural Product Research, 2019)

Enhancement of T Follicular Helper Cell-Mediated Humoral Immunity Reponses During Development of Experimental Autoimmune Myasthenia Gravis - Ying-Zhe Cui; Si-Ying Qu; Lu-Lu Chang; Jia-Rui Zhao; Lili Mu; Bo Sun; Hu-Lun Li; Tong-Shuai Zhang; Guang-You Wang; Qing-Fei Kong (Neuroscience Bulletin, 2019)

Fishery biology of whitespotted conger Conger myriaster (Brevoort, 1856) in the Yellow Sea and East China Sea - Xiuxia Mu; Chi Zhang; Ying Xue; Chongliang Zhang; Binduo Xu; Yiping Ren (Acta Oceanologica Sinica, 2019)

Blockade of Endogenous Angiotensin-(1–7) in Hypothalamic Paraventricular Nucleus Attenuates High Salt-Induced Sympathoexcitation and Hypertension - Xiao-Jing Yu; Yu-Wang Miao; Hong-Bao Li; Qing Su; Kai-Li Liu; Li-Yan Fu; Yi-Kang Hou; Xiao-Lian Shi; Ying Li; Jian-Jun Mu; Wen-Sheng Chen; Wei Cui; et al. (Neuroscience Bulletin, 2019)

Molecular surveillance of Vittaforma-like microsporidia by a small-volume procedure in drinking water source in Taiwan: evidence for diverse and emergent pathogens - Jung-Sheng Chen; Bing-Mu Hsu; Hsin-Chi Tsai; Yu-Pin Chen; Tung-Yi Huang; Kuan-Ying Li; Dar-Der Ji; Herng-Sheng Lee (Environmental Science and Pollution Research, 2018)

Analysis of the function of KIF3A and KIF3B in the spermatogenesis in Boleophthalmus pectinirostris - Yong-Qiang Zhao; Dan-Li Mu; Di Wang; Ying-Li Han; Cong-Cong Hou; Jun-Quan Zhu (Fish Physiology and Biochemistry, 2018)

Toxicity of Chlorpyrifos and Dimethoate to the Ciliate Urostyla grandis, with Notes on Their Effects on Cell Ultrastructure - Weijie Mu; Alan Warren; Xuming Pan; Chen Ying (Journal of Ocean University of China, 2018)

Cadmium and lead accumulations and agronomic quality of a newly bred pollution-safe cultivar (PSC) of water spinach - Ying-Ying Huang; Yang-Xiu Mu; Chun-Tao He; Hui-Ling Fu; Xue-Song Wang; Fei-Yue Gong; Zhong-Yi Yang (Environmental Science and Pollution Research, 2018)

Temperature signals in tree-ring width and divergent growth of Korean pine response to recent climate warming in northeast Asia - Xiaochun Wang; Minhua Zhang; Ying Ji; Zongshan Li; Mu Li; Yuandong Zhang (Trees, 2017)

The effects of CYP1A inhibition on alkyl-phenanthrene metabolism and embryotoxicity in marine medaka (Oryzias melastigma) - Jingli Mu; Fei Jin; Juying Wang; Ying Wang; Yi Cong (Environmental Science and Pollution Research, 2016)

Methylenebisnicotiflorin: a rare methylene-bridged bisflavonoid glycoside from ripe Pu-er tea - Mu-Ke Tao; Min Xu; Han Zhang; Hui Chen; Chang Liu; Hong-Tao Zhu; Dong Wang; Chong-Ren Yang; Ying-Jun Zhang (Natural Product Research, 2016)

Association of Optic Radiation Integrity with Cortical Thickness in Children with Anisometropic Amblyopia - Shun Qi; Yun-Feng Mu; Long-Biao Cui; Rong Li; Mei Shi; Ying Liu; Jun-Qing Xu; Jian Zhang; Jian Yang; Hong Yin (Neuroscience Bulletin, 2016)

IL-1α-induced microvascular endothelial cells promote neutrophil killing by increasing MMP-9 concentration and lysozyme activity - Xiaoye Liu; Hong Dong; Mingming Wang; Ying Gao; Tao Zhang; Ge Hu; Huiqing Duan; Xiang Mu (Immunologic Research, 2016)

Morphology, sex steroid level and gene expression analysis in gonadal sex reversal of triploid female (XXX) rainbow trout (Oncorhynchus mykiss) - Gefeng Xu; Tianqing Huang; Xian Jin; Cunhe Cui; Depeng Li; Cong Sun; Ying Han; Zhenbo Mu (Fish Physiology and Biochemistry, 2016)

Seasonal difference of human adenoviruses in a subtropical river basin based on 1-year monthly survey - Chi-Wei Tao; Bing-Mu Hsu; Po-Min Kao; Wen-Chien Huang; Tsui-Kang Hsu; Ying-Ning Ho; Yen-Ju Lu; Cheng-Wei Fan (Environmental Science and Pollution Research, 2016)

Effects of inefficient transcription termination of rbcL on the expression of accD in plastids of Arabidopsis thaliana - Baoye He; Ying Mu; Wei Chi (Photosynthesis Research, 2015)

Glucocorticoid Receptor β Acts as a Co-activator of T-Cell Factor 4 and Enhances Glioma Cell Proliferation - Qian Wang; Pei-Hua Lu; Zhi-Feng Shi; Yan-Juan Xu; Jie Xiang; Yan-Xia Wang; Ling-Xiao Deng; Ping Xie; Ying Yin; Bin Zhang; Hui-Jun Mu; Wei-Zhen Qiao; et al. (Molecular Neurobiology, 2015)

Prevalence, quantification, and typing of human adenoviruses detected in river water in Taiwan - Zhon-Min Huang; Bing-Mu Hsu; Po-Min Kao; Tien-Yu Chang; Tsui-Kang Hsu; Ying-Ning Ho; Yi-Chun Yang; Yu-Li Huang (Environmental Science and Pollution Research, 2015)

Safety and efficacy study of lung cancer stem cell vaccine - Mao Lin; Shu-Ying Li; Ke-Cheng Xu; Zheng-Ping Liu; Feng Mu; Yuan-Ying Yuan; Xiao-Hua Wang; Ji-Bing Chen; Qiao Li (Immunologic Research, 2015)

LNA-modified isothermal oligonucleotide microarray for differentiating bacilli of similar origin - Jing Yan; Ying Yuan; Runqing Mu; Hong Shang; Yifu Guan (Journal of Biosciences, 2014)

Probabilistic ecological risk assessment of cadmium in the Bohai Sea using native saltwater species - Jingli Mu; Juying Wang; Ying Wang; Yi Cong; Zhifeng Zhang (Acta Oceanologica Sinica, 2014)

The Adhesion AND Growth of Both the Human Primary Gingival Epithelial Cells and Streptococcus Mutans on Micro-Arc Oxidized Titanium - Jiangning Lv; Hongwei Li; Ying Mu; ShuMin Wang; Jing Sun; Jun Jiang; Ping Ding; Baolin Liu (Cell Biochemistry and Biophysics, 2014)

The Association of RAB18 Gene Polymorphism (rs3765133) with Cerebellar Volume in Healthy Adults - Chih-Ya Cheng; Albert C. Yang; Chu-Chung Huang; Mu-En Liu; Ying-Jay Liou; Jaw-Ching Wu; Shih-Jen Tsai; Ching-Po Lin; Chen-Jee Hong (The Cerebellum, 2014)

The Protective Effect of a Metallic Selenopeptide with Superoxide Dismutase and Glutathione Peroxidase Activities Against Alcohol Induced Injury in Hepatic L02 Cells - Wang Cheng; Shen Na; Yan Gang-lin; Sui Chun-hong; Zhuang Jian-jian; Lü Shao-wu; Luo Gui-min; Mu Ying (International Journal of Peptide Research and Therapeutics, 2014)

Intraperitoneal delivery of paclitaxel by poly(ether-anhydride) microspheres effectively suppresses tumor growth in a murine metastatic ovarian cancer model - Ming Yang; Tao Yu; Joseph Wood; Ying-Ying Wang; Benjamin C. Tang; Qi Zeng; Brian W. Simons; Jie Fu; Chi-Mu Chuang; Samuel K. Lai; T.-C. Wu; Chien-Fu Hung; et al. (Drug Delivery and Translational Research, 2014)

The Novel Heterocyclic Trioxirane [(1,3,5-Tris Oxiran-2-yl)Methyl)-1,3,5-Triazinane-2,4,6-Trione (TATT)] Exhibits a Better Anticancer Effect than Platinum-Based Chemotherapy by Induction of Apoptosis and Curcumin Further Enhances its Chemosensitivity - Chun-Li Su; Ying-Ti Wang; Mu-Hsin Chang; Kang Fang; Kwunmin Chen (Cell Biochemistry and Biophysics, 2014)

Rice black-streaked dwarf virus genome segment S5 is a bicistronic mRNA in infected plants - Jian Yang; Heng-Mu Zhang; Lu Ying; Jing Li; Ming-Fang Lv; Li Xie; Pei-Pei Li; Xiao-Ya Liu; Dai Liang-Ying; Jian-Ping Chen (Archives of Virology, 2014)

Aquatic predicted no-effect concentration for three polycyclic aromatic hydrocarbons and probabilistic ecological risk assessment in Liaodong Bay of the Bohai Sea, China - Ying Wang; Juying Wang; Jingli Mu; Zhen Wang; Ziwei Yao; Zhongsheng Lin (Environmental Science and Pollution Research, 2014)

Interleukin-1 beta C-511T polymorphism modulates functional connectivity of anterior midcingulate cortex in non-demented elderly Han males - Pei-Chi Tu; Tung-Ping Su; Chu-Chung Huang; Albert C. Yang; Heng-Liang Yeh; Chen-Jee Hong; Ying-Jay Liou; Mu-En Liu; Ching-Po Lin; Shih-Jen Tsai (Brain Structure and Function, 2014)

A correlation between acute kidney injury and myonecrosis after scheduled percutaneous coronary intervention - Min Zhang; Hao-yu Meng; Ying-ming Zhao; Zhi-wen Tao; Xiao-xuan Gong; Ze-mu Wang; Bo Chen; Zheng-xian Tao; Chun-jian Li; Tie-bing Zhu; Lian-sheng Wang; Zhi-jian Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Environmental capacity of petroleum hydrocarbon pollutants in Jiaozhou Bay, China: Modeling and calculation - Keqiang Li; Ying Su; Jun Ying; Xiulin Wang; Jinbo Mu (Journal of Ocean University of China, 2013)

Repeat oral dose toxicity studies of melamine in rats and monkeys - Richard J. Early; Hong Yu; Xueyan Peter Mu; Haiyan Xu; Lei Guo; Qingxue Kong; Junma Zhou; Bruce He; Xiuying Yang; Hailiang Huang; Edward Hu; Ying Jiang (Archives of Toxicology, 2013)

Molecular characterization of Chinese Hop stunt viroid isolates reveals a new phylogenetic group and possible cross transmission between grapevine and stone fruits - Zhixiang Zhang; Ying Zhou; Rui Guo; Lingxiao Mu; Yuanai Yang; Shifang Li; Hongqing Wang (European Journal of Plant Pathology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Molybdenum improves antioxidant and osmotic-adjustment ability against salt stress in Chinese cabbage (Brassica campestris L. ssp. Pekinensis) - Mu Zhang; Chengxiao Hu; Xiaohu Zhao; Qiling Tan; Xuecheng Sun; Anyong Cao; Min Cui; Ying Zhang (Plant and Soil, 2012)

Clinical significance of peritumoral lymphatic vessel density and lymphatic vessel invasion detected by D2-40 immunostaining in FIGO Ib1-IIa squamous cell cervical cancer - Ying Xiong; Li-Ping Cao; Hui-Lan Rao; Mu-Yan Cai; Li-Zhi Liang; Ji-Hong Liu (Cell and Tissue Research, 2012)

Degenerate primer design to clone the human repertoire of immunoglobulin heavy chain variable regions - Ying Sun; Hong-Yan Liu; Ling Mu; En-Jie Luo (World Journal of Microbiology and Biotechnology, 2012)

The interaction between ubiquitin C-terminal hydrolase 37 and glucose-regulated protein 78 in hepatocellular carcinoma - Ying Fang; Jingui Mu; Yushui Ma; Duan Ma; Da Fu; Xizhong Shen (Molecular and Cellular Biochemistry, 2012)

The genetic profiling of preferentially expressed genes in murine splenic CD8α+ dendritic cells - Tao Li; Wu-Ying Li; Hui-Ling Bai; Hong-Bing Ma; Hu Zhang; Jiang-Mu Zhu; Xiao-Hong Li; Hong-Ying Huang; Yuan-Fang Ma; Xin-Ying Ji (Immunologic Research, 2011)

Combination of Hyaluronic Acid Hydrogel Scaffold and PLGA Microspheres for Supporting Survival of Neural Stem Cells - Ying Wang; Yue Teng Wei; Zhao Hui Zu; Rong Kai Ju; Mu Yao Guo; Xiu Mei Wang; Qun Yuan Xu; Fu Zhai Cui (Pharmaceutical Research, 2011)

Molecular characterization and association analysis of FBXO40 with partial hematological indexes in pig - Z. W. Wang; X. Y. Li; Z. L. Tang; S. L. Yang; Z. Z. Ying; T. Fu; B. Fan; Y. L. Mu; H. Ao; K. Li (Molecular Biology Reports, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Alu tandem sequences inhibit GFP gene expression by triggering chromatin wrapping - Xiu-Fang Wang; Xiaoyan Wang; Jing Liu; Jingjing Feng; Wenli Mu; Xiaojuan Shi; QinQing Yang; Xiaocui Duan; Ying Xie; Zhanjun Lu (Genes & Genomics, 2009)

Enhanced migration and CXCR4 over-expression in fibroblasts with telomerase reconstitution - Yi Qu; Meng Mao; Xihong Li; Lin Zhang; Xiang Huang; Chunlei Yang; Fengyang Zhao; Ying Xiong; Dezhi Mu (Molecular and Cellular Biochemistry, 2008)

Sulfotransferase 1A1 and glutathione S-transferase P1 genetic polymorphisms modulate the levels of urinary 8-hydroxy-2′-deoxyguanosine in betel quid chewers - Ruey-Hong Wong; Chiung-Wen Hu; Ching-Ying Yeh; Mu-Rong Chao; Chin-Chun Chen; Jun-Huang Huang; Shih-Hsien Chang; Shin-I Lee; Hong-Shen Lee (Archives of Toxicology, 2008)

A collection of 10,096 indica rice full-length cDNAs reveals highly expressed sequence divergence between Oryza sativa indica and japonica subspecies - Xiaohui Liu; Tingting Lu; Shuliang Yu; Ying Li; Yuchen Huang; Tao Huang; Lei Zhang; Jingjie Zhu; Qiang Zhao; Danlin Fan; Jie Mu; Yingying Shangguan; et al. (Plant Molecular Biology, 2007)

PaCDPK1, a gene encoding calcium-dependent protein kinase from orchid, Phalaenopsis amabilis, is induced by cold, wounding, and pathogen challenge - Tsung-Mu Tsai; Ying-Ru Chen; Tien-Wen Kao; Wen-Su Tsay; Chiou-Ping Wu; Ding-Ding Huang; Wen-Huei Chen; Ching-Chun Chang; Hao-Jen Huang (Plant Cell Reports, 2007)

Microbial production of 1,3-propanediol from glycerol by Klebsiella pneumoniae under micro-aerobic conditions up to a pilot scale - Hai-Jun Liu; Dai-Jia Zhang; You-Hai Xu; Ying Mu; Ya-Qin Sun; Zhi-Long Xiu (Biotechnology Letters, 2007)

Microbial production of 1,3-propanediol by Klebsiella pneumoniae using crude glycerol from biodiesel preparations - Ying Mu; Hu Teng; Dai-Jia Zhang; Wei Wang; Zhi-Long Xiu (Biotechnology Letters, 2006)

Pharmacokinetic study with N-Ile1-Thr2-63-desulfato-r-hirudin in rabbits by means of bioassay - Guo-zhu Han; Hong-can Ren; Yong Lu; Ying Li; Shu Xiao; Hong-wei Ye; He-mu Wang (Journal of Zhejiang University-SCIENCE B, 2006)

The role of earthworms (Eisenia fetida) in influencing bioavailability of heavy metals in soils - Bei Wen; Xiao-yu Hu; Ying Liu; Wei-sheng Wang; Mu-hua Feng; Xiao-quan Shan (Biology and Fertility of Soils, 2004)